Economy entomology - Adams, Joshua William (My University, 1898)
Introduction: In preparing this paper it is not our intention to make it an encyclopedia of general information on the subject of economic entomology, nor do we expect to give an exhaustive discussion of any particular branch of the subject our only aim will be to call attention to the great and growing importance of this subject to the farming class in general and especially to the horticulturist.
Citation: Adams, Joshua William. Economy entomology. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Economic Entomology; Farming Class; Horticulturists; Theses; Manuscripts (documents)